Boron Phenylalanine-Modified Polydopamine Nanoparticles for Targeted Delivery of Danusertib in Non-Small Cell Lung Cancer - Xu Y; Chen X; Zhang L; Li P; He J; Zhu M; Makvandi P; Jin X (International Journal of Nanomedicine, 2025)
Yi Xu,1,* Xiang Chen,2,* Lin Zhang,3 Ping Li,3 Jiahuan He,3 Meiyu Zhu,3 Pooyan Makvandi,4 Xuru Jin2,3 1Department of Urology, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, Zhejiang, 324000, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of China; 3Department of Respiratory and Critical Care Medicine, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, Zhejiang, 324000, People’s Republic of China; 4Zhejiang Provincial Research & Engineering Center for Endoscopic Instrument, Department of Science & Technology, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, Zhejiang, 324000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuru Jin, Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Wenzhou Medical University, Shangcai Village, Nanbaixiang, Ouhai District, Wenzhou, Zhejiang, 325000, People’s Republic of China, Tel +86-13857782369, Email xuru.jin@wmu.edu.cn Pooyan Makvandi, Zhejiang Provincial Research & Engineering Center for Endoscopic Instrument, Department of Science & Technology, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, Quzhou, Zhejiang, 324000, People’s Republic of China, Email Pooyan.Makvandi@wmu.edu.cnPurpose: Aurora-A is often overexpressed in lung cancer and is associated with poor prognosis, making it a potential therapeutic target for non-small cell lung cancer (NSCLC) treatment. This study aimed to evaluate the therapeutic potential of nanomedicine-based delivery of the Aurora-A inhibitor Danusertib (Danu) in NSCLC treatment.Methods: Boron phenylalanine (BPA)-modified polydopamine (PDA) was used as a carrier to load Danu, preparing B-PDA@Danu nanoparticles. The structure, microstructure, particle size, zeta potential, stability, drug loading capacity, loading rate, and in vitro release were characterized. In vitro studies investigated its effects on A549 cell viability, apoptosis, uptake ability, and cell cycle. In vivo studies examined its distribution and/or anti-tumor effects in subcutaneous xenograft tumors in mice. The anti-tumor effects and biosafety of B-PDA@Danu were studied in a subcutaneous xenograft tumor model in mice. The in vivo distribution and anti-tumor effects of B-PDA@Danu were studied in a mouse lung carcinoma in situ model.Results: The synthesized B-PDA@Danu nanoparticles were spherical, negatively charged, with an average particle size of (172.96± 1.61) nm, exhibited good stability, and efficiently loaded Danu. B-PDA@Danu promoted cellular uptake in vitro, inhibited cell viability (P < 0.001), induced G2/M cell cycle arrest (P < 0.001), and increased apoptosis (P < 0.001). In the subcutaneous xenograft tumor model, B-PDA@Danu suppressed tumor growth (P < 0.001), induced cell cycle arrest in tumor cells (P < 0.001), caused tumor tissue damage, and showed good biosafety. In the mouse lung carcinoma in situ model, B-PDA@Danu effectively targeted and accumulated at the site of carcinogenesis, leading to tumor shrinkage.Conclusion: B-PDA@Danu provides a novel nanomedicine approach for anti-NSCLC therapy that enables targeted tumor elimination with low potential toxicity. Keywords: boron phenylalanine, polydopamine, Danusertib, non-small cell lung cancer